Sheikh Ahmadu Bamba : selected poems - Bāmbā, Aḥmadū, 1852-1927. (Islamic Literatures: Texts and Studies, 2017)
While in exile in Gabon (1895-1902), Sheikh Ahmadu Bamba marked a historic moment with his poetry of resilience, pivotal to the cultural and religious transformation of the Murīds of Senegal. The qaṣāʾid (poems) included in this annotated edition, most of them hymns of praise to the qualities of Allāh and the Prophet Muḥammad, and professions of faith that demonstrate how to realize the precepts found in the Qur'ān, display the underlying elements of Sheikh Ahmadu Bamba's imaginative energy and poetic vision. They reveal a unifying poetic purpose and exemplify Ṣūfī literary traditions in subject matter, form, and versification and aim to explore the deepest regions of mysticism in search of the divine truth.